Anti-edematogenic and anti-granuloma activity of a synthetic curcuminoid analog, 5-(3,4-dihydroxyphenyl)-3-hydroxy-1-(2-hydroxyphenyl)penta-2,4-dien-1-one, in mouse models of inflammation - Hisamuddin, Nadia; Shaik Mohamed Mossadeq, Wan Mastura; Sulaiman, Mohd Roslan; Abas, Faridah; Leong, Sze Wei; Kamarudin, Nur Nadhirah; Ong, Hui Ming; Ahmad Azmi, Ahmad Farhan; Mohammad Rasol, Rasyidah Ryta Ayumi; Abdul Talib, Madihah (MDPI, 2019)
Curcumin, derived from the rhizome Curcuma longa, has been scientifically proven to possess anti-inflammatory activity but is of limited clinical and veterinary use owing to its low bioavailability and poor solubility. Hence, analogs of curcuminoids with improved biological properties have been synthesized to overcome these limitations. This study aims to provide the pharmacological basis for the use of 5-(3,4-dihydroxyphenyl)-3-hydroxy-1-(2-hydroxyphenyl)penta-2,4-dien-1-one (DHHPD), a synthetic curcuminoid analog, as an anti-edematogenic and anti-granuloma agent. The carrageenan-induced paw edema and the cotton pellet-induced granuloma assays were used to assess the anti-inflammatory activity of DHHPD in mice. The effects of DHHPD on the histaminergic, serotonergic, and bradykininergic systems were determined by the histamine-, serotonin-, and bradykinin-induced paw edema tests, respectively. DHHPD (0.1, 0.3, 1, and 3 mg/kg, intraperitoneal) evoked significant reductions (p < 0.05) in carrageenan-induced paw edema at different time intervals and granuloma formation (p < 0.0001) by 22.08, 32.57, 37.20, and 49.25%, respectively. Furthermore, DHHPD significantly reduced paw edema (p < 0.05) induced by histamine, serotonin, and bradykinin. The present study suggests that DHHPD exerts anti-edematogenic activity, possibly by inhibiting the synthesis or release of autacoid mediators of inflammation through the histaminergic, serotonergic, and bradykininergic systems. The anti-granuloma effect may be attributed to the suppression of transudative, exudative, and proliferative activities associated with inflammation.